Cardiorespiratory function on swimmers with relaxed versus contracted abdominal muscles - Pankey, R.; Henrich, T.; Clay, C.; Hobbs, M. (Research Quarterly for Exercise and Sport, 2009)
Purpose: Pulmonary function does not limit exercise capacity because postures and segmental movements produced during activity do not impede the ventilatory muscles and there is time between segmental movements to ventilate the lungs adequately. In the competitive swimming Crawl Stroke (CS) the position of the head in the water and movement sequence permits adequate pulmonary ventilation and ventilation has not been shown to limit CS performance. Some sport theorists have suggested that posture should be altered during CS to decrease the hydrodynamic resistance to increase speed. However, postural alteration has never been documented to improve performance and it may impose limits on the cardiorespiratory system. The proposal changes in posture involve contracting the abdominal muscles, obliques and muscles controlling the lumbar spine to keep the body streamlined. We hypothesized that this posture interferes with the coordination of movement between the abdominal muscles and the diaphragm while simultaneously working in direct opposition to the accessory respiratory muscles limiting the swimmer's ability to ventilate air and consume oxygen. Prior to initiating a logistically complex study of swimmers in the water we developed this pilot study to determine if contracted muscles negatively affected pulmonary ventilation and oxygen consumption measured in a controlled laboratory setting.